Optimization of Nutrition Service Planning and Organization for Improving Public Health - Gabriela Vanesa Mutiarani; Nabila Salsabila (Professorline, 2026)
Optimization of nutrition services is one of the strategic efforts in improving public health through the provision of effective and efficient nutrition services. This article discusses the importance of careful planning and systematic organization in nutrition services, including in hospitals, health centers, schools, and the food industry. Planning includes identifying people's nutritional needs, prioritizing programs, and developing operational standards, while organization includes task sharing, resource management, and monitoring and evaluation mechanisms. With the implementation of this strategy, nutrition services become more structured, on target, and able to improve the quality of nutrition interventions. Optimizing nutrition service planning and organization also has an impact on reducing the risk of malnutrition, increasing public awareness about healthy eating, and improving overall public health. The results of this study emphasize that the integration between planning and organization is the key to the success of sustainable nutrition services.